Islamic Boarding School: Transformation of the Education System from Traditional to Modern - Ucu Somali; Imam Tabroni; Nur Aisah Jamil (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Indonesian people realize it or not, there is a dualism in education: General Education and Religious Education. One type of religious education (in this case Islam) is